Analysis of Factors Influencing the Economic Welfare of Fishermen's Households in The Coastal Area of Ambon City - Soselisa, Hobarth Williams (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
The economic welfare of fishermen's households in the coastal areas of Ambon City is influenced by various interrelated factors. This study aims to identify and analyze the factors that play a role in the economic welfare of fishermen's households, such as education level, asset ownership, access to capital, environmental conditions, and government policies in supporting the fisheries sector. A qualitative approach was used in this study, with data collection methods through surveys and interviews with fishermen in several coastal areas of Ambon City. The results of the study revealed that asset ownership and access to capital have a significant impact on the income of fishermen's households, while education level contributes to improving managerial skills and business diversification. In addition, the condition of the aquatic environment and government policies, including fisheries assistance and infrastructure, also determine the level of fishermen's welfare. Therefore, this study recommends increasing access to capital, skills training for fishermen, and strengthening sustainability-based policies to support improving the economic welfare of fishermen's households in Ambon City.